Review of the Eriococcidae (Hemiptera: Coccomorpha) infesting Fabaceae in Argentina, with descriptions of three new species of Acanthococcus Signoret - González, Patricia; Claps, Lucía E.; Juárez, Andrea; Moreno, Diego (Zootaxa, 2017)
Three new species of Eriococcidae from Argentina, namely Acanthococcus haywardi Juárez & González sp. nov., A. punctatae Juárez & González sp. nov. and A. riojensis Juárez & González sp. nov., are described and illustrated, bringing the total number of eriococcid species now known from Argentina to 12, of which six belong to Acanthococcus Signoret and six to Hempelicoccus Kozár. They are found on 11 species of Fabaceae (subfamilies Mimosoideae and Caesalpinioidae), are widely distributed and are all restricted to the Neotropical region and the South American Transitional Zone. A key to the 12 Eriococcidae species now known on Fabaceae in Argentina is included.